Health monitor circuit for automatic meteorological Data collection systems - VASHISTHA, R. D. (MAUSAM, 1983)
A circuit is described for monitoring at the receiving end of an automatic meteorological data collection system, the quality of the data received from remote automatic field terminal station. The received data quality is monitored in terms of the received data for certain prefixed levels of reference voltage transmitted from field. The circuit gives a go-nogo type indication depending on whether or not the reference data levels are received within the prescribed limits and it becomes possible at the data receiving and processing terminal to decide upon the useful part of the incoming data to, be processed and printed out. Additionally the circuit gives the sign of those parameters which can go either positive or negative like temperature. The circuit is elegant yet simple in design and gives trouble free operation.